SIGNIFICANCE OF SIRODHARA IN MANASIKA ROGA - Y.Ratna Priya Darsini (International Journal of Applied Ayurved Research, 2017)
In modern developed world, we have an active and turbulent culture. We ever desire new things and seldom content with what we have. As a result of this, human psyche has failed to cope with rapid change of pattern, life-style, and fast progress of technological and industrial developments. .This ultimately resulted in the feeling of loneliness, not being appreciated, anger, stress and anxiety. Ayurveda considers alpasatwa as the most important cause of manasika vikaras. Vata is said to be the controller and promoter of manas. Ayurveda has recognized the inter-dependent relationship of mind and body, and has a clear concept about psychosomatic approach. Dhara considered as one of the specialities of Keraliya panchakarma is a process of running a fine stream of liquid medicaments for a stipulated period of time. It is of three types and the present paper is limited to moordhanya dhara/sirodhara and its significance in the management of Manasika rogas like stress, psychosis etc.